Otite média e externa bilateral em cães : estudo comparativo do perfil microbiológico e susceptibilidade a antimicrobianos das especíeis prevalentes - Oliveira, Lis Christina de (2004)
Otitis results from auricular inflammation and represents 8-15% of all cases received in the veterinarian practices. This study was done to outline and compare the isolation profile in external and middle ears from dogs with otitis. Between August/2003 and March/2004, 64 dogs with both otitis externa and media and 50 dogs with bilateral otitis externa were studied. Fifty dogs with healthy ears were used as control group. The collection was done ate the Zoonosis Control Center in Fortaleza-CE and the microbiological analysis at the Microbiological Center - Department of Pathology and Legal Medicine-UFC. Samples from the external ears were collected with sterile swabs and the ones from the middle ears by osteotomy of the tympanic bulla. The microrganisms were cultured and identified according to methods previously described and susceptibility tested by agar diffusion method (NCCLS). In otitic dogs the most frequent alterations were: lesions of the pinna (72%), local pain (12%) and alteration of the pinna position (12%). Sixty-two per cent of the dogs showed entire tympanic membrane with some structural alteration. Microbiogical growth was seen in 48% of the samples fromdogss with otitis media, and the most frequent isolates were: Estafilococos positive-coagulase (62.5%), non-fermentative Gram-negative (10%), Enterobacteriaceae (5%) and Candida albicans (5%). It was observed that there was an increased number and variety of species isolated in external ears comparaed to middle ears. In samples from external ears, the following predominated: Bacillus sp. (27.1%), M. pachydermatis (23.4%) e S. intermedius (21.8%). The most frequent species isolated in dogs with bilateral otitis externa were: Bacillus sp. (27.9% e 31%), M. pachydermatis (25.9% e 24%), S. intermedius (23.8% e 24.6%) e Enterobactérias (6% e 6.1%). There was a significative difference (p<0.0001) in the way the isolates were associated, which showed the individuality from each ear in bilateral otitis externa. In this study, no anaerobic microrganisms were isolated. S. intermedius strains (n=83) showed intermediate resistance to most of the cntimicrobials tested and high resistance to penicillin (36.1%), ampicillin (27.7%), tetracyclin (27.7%), erythromycin (14.5%) and clindamycin (12.0%). These results describe tha variety of bacterial and fungal isolates associated with canine otitis and reveal the need to adopt systematic procedures for the diagnosis and treatment of dogs with otitis.